Pigs might fly : a novel - King-Smith, Dick.; Rayner, Mary (New York : Viking Press, 1982)
A runt piglet born with deformed front feet is coached in swimming by a duck and an otter and, when the pig farm is flooded, becomes a hero.
London ed. published as: Daggie Dogfoot. 1980.
Keywords: Pigs -- Fiction; Farm life -- Fiction; England -- Fiction